Does Platelet-Rich Fibrin Decrease Dimensional Changes and Improve Postoperative Comfort in Post-Extraction Sockets? An Overview of Systematic Reviews - Vittorio Moraschini; Carlos Fernando de Almeida Barros Mourão; Rafael Coutinho de Mello Machado; Jhonathan Raphaell Barros Nascimento; Kayvon Javid; Monica Diuana Calasans-Maia; Angelo Cardarelli; Pietro Montemezzi; Jose de Albuquerque Calasans-Maia (Applied Sciences, 2020)
This overview aimed to evaluate the methods, quality, and outcomes of systematic reviews (SRs) conducted to investigate the effects of platelet-rich fibrin (PRF) in dental sockets on promoting bone regeneration and soft tissue healing and diminishing the incidence of pain, swelling, trismus, and alveolar osteitis after tooth extraction. An electronic search without date or language restriction was done in PubMed/MEDLINE, Cochrane, and Web of Science until March 2020. Eligibility criteria included SRs that assessed the effect of PRF for human alveolar socket preservation. The quality assessment of the included studies was performed using AMSTAR 2 guidelines. The protocol of this overview was recorded in PROSPERO under the number CRD42018089617. The search and selection process yielded 13 studies published between 2011 and 2018. The analysis of the studies showed inconclusive data for the effect of the PRF and the dimensional changes. There is no definitive evidence for the impact of using PRF alone on bone regeneration in post-extraction sockets. The use of PRF improves soft tissue healing and reduces pain, bleeding, and osteitis in post-extraction sockets.